Pengembangan Keterampilan Berpikir Kritis dalam Penerapan Kurikulum Merdeka di Sekolah Dasar - Salpid, Sitisyadiyatularopah; Sopyan, Arisal (MURABBI, 2025)
The independent curriculum is the latest innovation in basic education which aims to provide freedom and flexibility for teachers to choose and manage their own curriculum. One of the main goals of implementing the independent curriculum is to improve students' critical thinking skills. Critical thinking skills are important intellectual skills that prepare students to face the complexities of the modern world. The aim of this research is to evaluate the impact of implementing the independent curriculum on primary school students' critical thinking skills.  As educational institutions, schools have a responsibility to help students develop critical thinking skills.  This research uses the PTK type of research (Classroom Action Research). The research method involves collecting qualitative data through observation and interviews.  The subjects in this research were class IV students at SDN Tenjolaya IV, Kasomalang. Research shows that students' critical thinking abilities increased significantly after implementing the independent curriculum from previously getting 75% to 85% in the good category. Then followed by cycle II which has a higher percentage than cycle I, namely with a percentage of 85% higher and has a very good category.